2021
DOI: 10.1016/j.jadohealth.2021.09.010
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccine Sentiments Among African American or Black Adolescents in Rural Alabama

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(48 citation statements)
references
References 13 publications
(10 reference statements)
3
42
0
1
Order By: Relevance
“…If public authorities are the primary source of information about COVID-19, then trust in the authorities is critical to increase the willingness to obtain the vaccine. Populations that have a historical distrust in medical institutions due to previous medical abuse continue to report a lack of trust in vaccines (Budhwani et al 2021;Hall et al 2021;Jamison et al 2019). Bennett and colleagues highlight that receiving information from private medical professionals increases comfort to be vaccinated, however, all health care professionals do not feel competent in communicating with patients who are hesitant to be vaccinated which leaves public authorities to be the primary source of information that is viewed as credible (Paterson et al 2016;Shen and Dubey 2019).…”
Section: Willingness To Take the Covid-19 Vaccinementioning
confidence: 99%
“…If public authorities are the primary source of information about COVID-19, then trust in the authorities is critical to increase the willingness to obtain the vaccine. Populations that have a historical distrust in medical institutions due to previous medical abuse continue to report a lack of trust in vaccines (Budhwani et al 2021;Hall et al 2021;Jamison et al 2019). Bennett and colleagues highlight that receiving information from private medical professionals increases comfort to be vaccinated, however, all health care professionals do not feel competent in communicating with patients who are hesitant to be vaccinated which leaves public authorities to be the primary source of information that is viewed as credible (Paterson et al 2016;Shen and Dubey 2019).…”
Section: Willingness To Take the Covid-19 Vaccinementioning
confidence: 99%
“…The historical marginalization of African Americans contributes to health inequities, such as lack of safe transportation among injured Black pedestrians leading to higher hospitalization rates compared to injured White pedestrians [ 25 ]. History of being subjected to unethical clinical studies, such as the Tuskegee study, has contributed to the African American youth’s mistrust of the government and the healthcare system which results in low influenza vaccination rates [ 26 ], COVID-19 vaccination hesitancy [ 27 ], and higher susceptibility to dying from COVID-19 than other racial groups [ 28 ].…”
Section: Historical Traumamentioning
confidence: 99%
“…Reducing COVID-19 vaccine hesitancy in rural Alabama is a high-priority, urgently warranted public health target. Focusing on increasing HPV vaccine uptake and concurrently examining COVID-19 vaccine hesitancy are timely and warranted targets due to low rates of HPV vaccination and high levels of COVID-19 vaccine hesitancy [ 6 ], of which both are devastating African American populations in rural communities.…”
Section: Introductionmentioning
confidence: 99%
“…Although vaccine-focused health disparities research has indicated gaps in uptake [ 14 - 16 ], studies that hone in on vaccine hesitancy have noted reasons for these gaps. A recent study of adolescent perspectives in rural Alabama found significant misinformation and institutional distrust, which resulted in vaccine skepticism [ 6 ]. Additionally, since adolescents are often ambivalent or apathetic to behavior change, including seeking preventive health care [ 17 ], theoretical orientations that enhance motivation without critique or judgment have the potential to resolve barriers to vaccination.…”
Section: Introductionmentioning
confidence: 99%